Students' entrepreneurial behavior: international and gender differences - Tugrul Daim; Marina Dabic; Elvan Bayraktaroglu (Journal of Innovation and Entrepreneurship, 2016)
Due to a high level of uncertainty, entrepreneurship is generally considered a risky endeavor. This paper explores the factors impacting entrepreneurial behavior in order to identify new educational opportunities for its development. The paper explores perceived feasibility and desirability for students in 10 countries. The entrepreneurship role is gender tested against desirability and feasibility. The requirements for developing this skill set are also studied. A survey instrument was developed, and data was collected from 4281 students. The results indicate that gender impacts entrepreneurship intention and the way it impacts is influenced by which country the students are from.
Keywords: 650; Entrepreneurship; International differences; Gender differences; Behavior; Higher education